Pathoanatomy and computed tomography classification of glenoid fossa fractures based on ninety patients - Bartoníček, Jan; Tuček, Michal; Klika, Daniel; Chochola, Antonín (International orthopaedics, 2016)
PURPOSE: The aim of the article is to present the pathoanatomy and a new classification of glenoid fractures developed on the basis of analysis of 3D computed tomography (CT) examinations and intra-operative findings. MATERIALS AND METHODS: The study group comprised 90 patients (69 men and 21 women) who sustained glenoid fractures. Mean patient age was 47 years (17-92). In 77 nonpolytraumatised patients, anteroposterior (AP) radiographs of the affected shoulder girdle were taken, including Neer I and II views. All 90 patients underwent CT examination, combined in 73 of them with 3D CT reconstruction including subtraction of the humeral head, ribs and clavicle, from the anterior and posterolateral views. In total, 52 patients (58 %) were operated on and 38 42 %) were treated non-operatively. RESULTS: In total, five basic types of injuries to the glenoid were identified based on analysis of the separated portion of the glenoid fossa: including fractures of the superior glenoid (14 cases, 16 %), the anterior glenoid (23 cases, 23 %), the posterior rim of the glenoid (5 cases, 6 %), the inferior glenoid (38 cases, 42 %) and the entire glenoid (10 cases, 11 %). CONCLUSION: The proposed classification of glenoid fractures defines five basic types of fractures verified by 3D CT reconstructions and intra-operative findings. It respects the anatomical architecture of scapula, fracture mechanism, associated injuries to the shoulder girdle and, where appropriate, the preferred surgical approach.
Keywords: dospělí; senioři nad 80 let; Tomography, X-Ray Computed; retrospektivní studie; Humans; lidé středního věku; Middle Aged; Aged, 80 and over; Young Adult; Shoulder Injuries; peroperační doba; mladý dospělý; zobrazování trojrozměrné; kloubní jamka lopatky; mužské pohlaví; Physical Examination; fraktury kostí; Adult; Adolescent; fyzikální vyšetření; Fractures, Bone; ramenní kloub; ženské pohlaví; Imaging, Three-Dimensional; lidé; Glenoid Cavity; mladiství; Shoulder Joint; počítačová rentgenová tomografie; Aged; senioři; poranění ramene; Male; Retrospective Studies; Intraoperative Period; Female